The Role of Automated Writing Assessment: University Students’ Views on Writing Performance and Self-Regulation - Ita Sari Ziadah Rohmah; Alfan Zuhairi (Educazione: Journal of Education and Learning, 2025)
This study investigates how artificial intelligence (AI) supports students’ self-regulated writing (SRW) practices in academic contexts, particularly in thesis writing. Adopting a qualitative case study design, the research involved six final-year students in an English Language Education program, selected through purposive sampling to represent varying levels of AI reliance. Data were collected through Likert-scale questionnaires and semi-structured interviews, then analyzed using descriptive statistics and thematic analysis. The findings indicate that students predominantly use AI tools for text-processing tasks such as grammar correction, paraphrasing, and translation, which contribute to improved writing accuracy, efficiency, and confidence. However, AI is less consistently utilized for higher-order processes, including idea development and progress monitoring, reflecting varied levels of metacognitive engagement. The results also reveal that students strongly prefer combining AI-generated feedback with input from teachers and peers, particularly for conceptual and substantive revisions. While AI enhances motivation and supports certain aspects of self-regulation, concerns about over-reliance and reduced critical engagement persist. These findings suggest that AI functions most effectively as a complementary tool within a broader pedagogical framework rather than as a substitute for human interaction. The study highlights the importance of integrating AI literacy and metacognitive training into academic writing instruction to ensure that students can use AI tools critically and strategically.